Kinetic Study of Paracetamol Degradation with Advanced Oxidation Process (AOP) Combination of Ozone, Hydrogen Peroxide and Ultraviolet (O3/H2O2/UV) - Tarigan, Azarya Yoseph; Effendi, Agus Jatnika (PT FORMOSA CENDEKIA GLOBAL, 2024)
Paracetamol is an analgesic and antipyretic drug commonly used by the public, with consumption reaching thousands of tons per year. Paracetamol, also known as acetaminophen, consists of a benzene ring core substituted by a hydroxyl group and a nitrogen atom. Paracetamol is not easily adsorbed or biologically degraded, which raises significant concerns about its impact on humans and the environment. One of the commonly used conventional treatments for paracetamol involves chlorine, which produces hazardous by- products such as 1,4-benzoquinone and N-acetyl-p-benzoquinone imine. Therefore, a better and safer method is needed for the treatment of paracetamol. Advanced Oxidation Processes (AOPs) are proven methods for treating difficult-to-degrade organic compounds and converting them into simpler compounds. AOPs utilize free radicals to oxidize pollutant compounds, transforming them into more manageable forms. The performance of AOPs can be enhanced by combining oxidants such as ozone, hydrogen peroxide, and ultraviolet light. Hence, in this research, the AOP method is employed to treat paracetamol, and the study aims to analyze the kinetics, efficiency, and by-products of this AOP method